PERANAN BADAN USAHA MILIK DESA (BUMDes) ARWANA MAHATO DALAM MENINGKATKAN POTENSI DAN KESEJAHTERAAN MASYARAKAT DI DESA MAHATO - Lesra Mardoni (CV.Karoteh Utama, 2023)
This study aims to determine the role of BUMDes Arwana Mahato in increasing village community participation, the role of BUMDes in realizing an independent village, policies developed to support community participation towards an independent village. The research method used is descriptive with data collection techniques including in-depth interviews, observation, and documentation. Data analysis techniques are descriptive quantitative and descriptive qualitative. The results of the study show that the role of BUMDes Arwana Mahato is in increasing community participation through training, outreach and coaching, creating employment opportunities for the community and fostering community business activities. The role of BUMDes in realizing an independent village is to increase the potential and welfare of the community through employment, growing community economic activities, providing easy access to business, and increasing village original income (PADes). The policies developed to support community participation towards an independent village are coordination with the village government supervising the management of BUMDes, cooperation with local governments and BUMDes business partners in conducting training.